KAJIAN POTENSI ESTROGENIK EKSTRAK n-HEKSAN HERBA KEMANGI (Ocimum americanum L.) PADA TIKUS PUTIH BETINA (Rattus norvegicus) - E. Mulyati Effendi; Anatria Kholiyah (Universitas Pakuan, 2014)
Menopause is a condition in which menstrual cycles stalled due to gland gonadotropin no longer carry out their duties in work affecting the ovaries to produce estrogen. Will halt production of estrogen can lead to osteoporosis (bone loss), kolesterolemia and heart disease. Basil herbs contain chemicals suspected of having estrogenic activity. This study aims to determine the optimum dose estrogenic activity and n-hexane extractof herbs basil (Ocimum americanum L.). animal testing is used 25 female rats were divided into 5 treatment groups. The result showed that all three doses of n-hexane extract of basil herbs have estrogenic activity. The average increase in estrous cycle in groups III, IV and V was 143 hours, 144,6 hours, and 148,6 hours, while the average of scoring against ovarian and uterine vascularitation in group III, IV and V are 2,2; 2 and 2,4. In weighing the ovaries and uterus weights on average in groups III, IV and V are 1,36 g, 1,72 g and 1,7 g. From the above result it can be oncluded that n-hexane extracts of basil herb can cause estrogenic activity with an effective dose of 0,2 g/200g BW.Key words: Basil (Ocimum americanum L.), estrogen wung, n-Heksan